2017
DOI: 10.18203/2394-6040.ijcmph20171783
|View full text |Cite
|
Sign up to set email alerts
|

A community based cross sectional study to assess the drinking water handling and management practices, sanitary practices at the household level in Sullia taluk, Karnataka

Abstract: Background: The Millennium Development Goals (MDGs) - 7 aimed to reduce by half the proportion of population without sustainable access to safe drinking water and basic sanitation by 2015. Without access to clean water and basic toilets, and without good hygiene practices, a child’s survival, growth and development are at risk. This study was conducted to assess the drinking water management and handling practices at household level of Sullia Taluk of Karnataka which would give an insight into drinking water m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…Similar results were seen in a study by Sharanya Kaniambady et al 5 Most of females were homemakers mostly engaged in household activity. The literacy status of women of majority of households was matriculation and above while 13.8% of them were illiterate.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were seen in a study by Sharanya Kaniambady et al 5 Most of females were homemakers mostly engaged in household activity. The literacy status of women of majority of households was matriculation and above while 13.8% of them were illiterate.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the respondents did not practice any water treatment method (68. 5%).Similar findings were also reported in a study by Venkatashiva et al done in households of Sugali Tribe of Chittoor District, and Sharanya Kaniambady et al 5,16 Only 16.5% of households used ladle to take out drinking water from vessel. Most of the respondents interviewed used water by directly drinking water collected in bottles.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another study by Kaniambady et al . [ 22 ] observed that 27% of slums all over India had no garbage disposal facility and revealed that majority of the slum population disposed their liquid wastes (68.3%) and solid waste (59.8%) haphazardly. [ 22 , 23 ] Similar results have been found in this study which revealed distorted ways of waste disposal among slum households.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] observed that 27% of slums all over India had no garbage disposal facility and revealed that majority of the slum population disposed their liquid wastes (68.3%) and solid waste (59.8%) haphazardly. [ 22 , 23 ] Similar results have been found in this study which revealed distorted ways of waste disposal among slum households. About 69.8% reported that they disposed the solid wastes at the community dumping spot set by the BMC, while 83% reportedly disposed liquid wastes in the open drainage system of kutcha origin.…”
Section: Discussionmentioning
confidence: 99%